An Ediacaran orogeny in subglacial East Antarctica is uncovered by detrital garnet geochronology - Sharmaine Verhaert; Stijn Glorie; Martin Hand; Jacob A. Mulder; Anthony R. Milnes; Jacqueline A. Halpin (Communications Earth & Environment, 2024)
Abstract Detrital minerals provide valuable insights into the tectonic history of continents. Uranium-lead dating of detrital zircon is widely used to characterize the magmatic history of continents but is generally insensitive to metamorphism accompanying the production and reworking of crust during orogenesis. Garnet is the most important mineral for recording prograde and peak orogenic metamorphism and can occur as a common detrital phase. Here, we demonstrate laser-ablation lutetium-hafnium (Lu-Hf) geochronology of detrital garnet as a provenance tool for reconstructing orogenic histories at (super)continental scales. Detrital garnet (n = 557) from modern sands and Permo-Carboniferous glacial strata in South Australia faithfully record local garnet-grade metamorphic events but also include a major population at ca. 590 million-years with no known source in South Australia. We trace the ca. 590 million-year-old detrital garnets to a largely ice-covered orogenic province in East Antarctica, uncovering the inception of convergent margin tectonism along the palaeo-Pacific margin of Gondwana.